Cyber crime and cyber terrorism investigator's handbook - Akhgar, Babak; Staniforth, Andrew; Bosco, Francesca M.; Elliot, Steve; Rearick, Benjamin; Kumaraguruparan, Priya; Rogers, Mark (Elsevier, 2014)
Cyber Crime and Cyber Terrorism Investigator's Handbook is a vital tool in the arsenal of today's computer programmers, students, and investigators. As computer networks become ubiquitous throughout the world, cyber crime, cyber terrorism, and cyber war have become some of the most concerning topics in today's security landscape. News stories about Stuxnet and PRISM have brought these activities into the public eye, and serve to show just how effective, controversial, and worrying these tactics can become. Cyber Crime and Cyber Terrorism Investigator's Handbook describes and analyzes many o